Analisis Lingkungan Kerja dan Kompetensi terhadap Kinerja Karyawan Bagian Produksi PT. Tjakrindo Mas Gresik - Afrizal Fikri Anugrah; Mei Retno Adiwati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
There are still problems in terms of employee performance making this research the main priority. The purpose of this research is: 1.) To determine the effect of the work environment on the performance of employees in the production department at PT. Tjakrindo Mas Gresik; 2.) To determine the effect of competence on the performance of employees in the production department at PT. Tjakrindo Mas Gresik. The data used is primary data, namely data collected through questionnaires distributed to employees of the production division of PT. Tjakrindo Mas Gresik and the sample used as many as 53 respondents. Likert scale is used as a measurement. The sampling technique used was saturated sampling technique. Meanwhile the analysis used is Partial Least Square (PLS). Based in the results of research conducted: 1.) The work environment can contribute to employee performance; 2.) Competence can contribute to employee performance